Expressional drawing and creativity: visual thought in benefit of the project - Moretto, Joicelaine (Corporación Universitaria del Caribe, CECAR., 2018)
ABSTRACT The present work has the objective of presenting, through bibliographic research, the drawing, specifically the one done manually in a fast way, seeking to clarify its characteristics and contributions to creativity. The term Expresional Drawing is used to describe fast manual graphical representations, replacing the terms sketch, sketch, sketch and rap (rough). The text also presents information from an experimental research, which aims to contribute to the culture of drawing practice as an auxiliary tool in the generation of ideas, during a process of problem solving, with the aim of benefiting areas such as Architecture and Design.